Bank Syariah di Pakistan - Nobon, Repina Wilda Otista (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
The development of Sharia Banking in Pakistan is a situation where people need alternative banking that implements an Islamic banking system that provides sound banking, banking and financial collection and services that meets Islamic principles. The purpose of this paper is to explain why and when Islamic Banking was introduced in Pakistan, to find out what Islamic banking products are commonly used in Pakistan, and how the Pakistani government builds and promotes these products so that they can grow rapidly. In this paper we analyze the progress made by Pakistan in developing the Islamic Banking System. This paper also briefly explains the introduction of Islamic Banking and the importance of Islamic banking in the world.